2003
DOI: 10.1128/aem.69.2.1327-1330.2003
|View full text |Cite
|
Sign up to set email alerts
|

UV Resistance of Bacillus anthracis Spores Revisited: Validation of Bacillus subtilis Spores as UV Surrogates for Spores of B. anthracis Sterne

Abstract: Recent bioterrorism concerns have prompted renewed efforts towards understanding the biology of bacterial spore resistance to radiation with a special emphasis on the spores of Bacillus anthracis. A review of the literature revealed that B. anthracis Sterne spores may be three to four times more resistant to 254-nmwavelength UV than are spores of commonly used indicator strains of Bacillus subtilis. To test this notion, B. anthracis Sterne spores were purified and their UV inactivation kinetics were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
111
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(120 citation statements)
references
References 12 publications
6
111
1
1
Order By: Relevance
“…Since several publications have shown that there are variations in Martian UV simulations (7,21,46), we UV irradiated spores of B. pumilus SAFR-032 and B. pumilus 168 using an alternate Martian UV simulation system developed at KSC (32). Spores of these organisms were exposed to Martian UV, UVA, UVAϩB, and full-spectrum irradiation conditions.…”
Section: Survival Of Endospores In Aqueous Solutions Under Simulated mentioning
confidence: 99%
See 1 more Smart Citation
“…Since several publications have shown that there are variations in Martian UV simulations (7,21,46), we UV irradiated spores of B. pumilus SAFR-032 and B. pumilus 168 using an alternate Martian UV simulation system developed at KSC (32). Spores of these organisms were exposed to Martian UV, UVA, UVAϩB, and full-spectrum irradiation conditions.…”
Section: Survival Of Endospores In Aqueous Solutions Under Simulated mentioning
confidence: 99%
“…However, there have been few studies that have tested the UV resistance of a diverse range of environmental strains of Bacillus species (28). Invariably, all microbial lethality assessments and sterilizer validation studies have been carried out using laboratory strains of B. subtilis and/or Geobacillus stearothermophilus (32). Microbes inhabiting nutrient-poor and dry spacecraft assembly facilities and the resistance traits of these organisms are important to the aerospace, medical, and pharmaceutical industries.…”
mentioning
confidence: 99%
“…For that reason, they are employed as biological indicators for monitoring the effectiveness of sterilization processes, such as vaporized hydrogen peroxide treatments (17,19), autoclaving, and UV irradiation (25,30).…”
mentioning
confidence: 99%
“…Therefore, the model of Chick-Watson, reduced to a first-order kinetic with n = 1, showing its limits, and that the inactivation process is most often non-uniform, and does not necessarily comply, as implies a first-order kinetics, with an exponential law (Shayeb et al, 1998;Nicholson and Galeano, 2003). In addition, the adopted experimental protocol showed a very noticeable reduction rate for low doses of irradiation.…”
Section: Modeling Of the Kinetics Of Disinfection By Uv Irradiationmentioning
confidence: 99%